Ethics in Cross-Cultural Translation : Understanding Cultural Sensitivity in Translation Work - Hafiza Saumi Ramadilla; Halimah Br Surbakti; Rita Hartati (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This research explores the role of ethics in cross-cultural translation, focusing on the essential principle of cultural sensitivity in translation work. In an increasingly globalized world, translation not only requires linguistic expertise but also the ability to navigate complex cultural landscapes. The research highlights the importance of understanding cultural nuances, ethical considerations, and the impact of translation on social responsibility. Through a literature review, the study examines various scholarly perspectives on translation ethics, drawing on the works of notable researchers and case studies. The methodology employed in this study is a comprehensive literature review, synthesizing insights from existing research on translation ethics, social responsibility, and cultural sensitivity. The findings emphasize that ethical translation is not merely about accurate word-for-word translation but involves a deeper awareness of cultural contexts and values. Translators must balance linguistic accuracy with the cultural meanings embedded in the source text, ensuring that the translated work resonates with the target audience while respecting cultural differences.